Structural Equation Modeling to Analyze the Critical Driving Factors and Paths for Off-site Construction in China - Mao, C.; Liu, G.; Shen, L.; Wang, Xiangyu; Wang, J. (Springer, 2017)
© 2017 Korean Society of Civil Engineers and Springer-Verlag GmbH Germany, part of Springer Nature Off-site Construction (OSC) is an alternative to conventional construction. However, China lags behind developed countries in terms of its OSC development. The chief goal of this study is to demonstrate the critical driving forces and solutions that promote OSC development. A total of 21 hypotheses are established to present the interrelations among eight driving forces. Based on 176 valid responses from developers in mainland China, a structural equation model is built to explore the key solutions and the critical driving forces. Most driving forces, such as Pursuit of Sustainable Competitiveness (PSC), Governmental Policies and Regulations (GPR), Technological Innovation (TI), Corporate Social Responsibility (CSR), and Construction Market Demand (CMD), can affect a Corporation’s Willingness and Behavior (CWB) in adopting OSC through two mediating factors, namely, Economic Benefits (EB) and social and environmental benefits. The findings highlight five main driving solutions to promote OSC, namely, “PSC ? EB ? CWB,” “PSC ? TI ? EB ? CWB,” “GPR ? TI ? EB ? CWB,” “GPR ? CSR ? CWB,” and “GPR ? CMD ? CWB.” Governments and project clients are also identified as important players in the development of OSC in China. These results provide a valuable reference for the government to understand the underlying interrelationships among the driving forces and key solutions to the development of OSC in China.